(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1863)
On the day, John Buchanan exhibited and donated some letters written by General James Wolfe to the Society’s collections. He highlights their provenance and importance to the study of Wolfe’s life and character. There is also some discussion of the person who the letters were addressed to, William Rickson.